Characterization and regulation of expression of an antifungal peptide from hemolymph of an insect, Manduca sexta. (August 2016) - Al Souhail, Qasim; Hiromasa, Yasuaki; Rahnamaeian, Mohammad; Giraldo, Martha C.; Takahashi, Daisuke; Valent, Barbara; Vilcinskas, Andreas; Kanost, Michael R.
Abstract: Insects secrete antimicrobial peptides as part of the innate immune response. Most antimicrobial peptides from insects have antibacterial but not antifungal activity. We have characterized an antifungal peptide, diapausin-1 from hemolymph of a lepidopteran insect, Manduca sexta (tobacco hornworm). Diapausin-1 was isolated by size exclusion chromatography from hemolymph plasma of larvae that were previously injected with a yeast, Saccharomyces cerevisiae . Fractions containing activity against S. cerevisiae were analyzed by SDS-PAGE and MALDI-TOF MS/MS and found to contain a 45-residue peptide that was encoded by sequences identified in M. sexta transcriptome and genome databases. A cDNA for diapausin-1 was cloned from cDNA prepared from fat body RNA. Diapausin-1 is a member of the diapausin family of peptides, which includes members known to have antifungal activity. The M. sexta genome contains 14 genes with high similarity to diapausin-1, each with 6 conserved Cys residues. Diapausin-1 was produced as a recombinant protein in Escherichia coli . Purified recombinant diapausin-1 was active against S. cerevisiae, with IC50 of 12 μM, but had no detectable activity against bacteria. Spores of some plant fungal pathogens treated with diapausin-1 had curled germination tubes or reduced and branched hyphal growth. Diapausin-1 mRNA level in fat body strongly increased after larvae were injected with yeast or with Micrococcus luteus . In addition, diapausin-1 mRNA levels increased in midgut and fat body at the wandering larval stage prior to pupation, suggesting developmental regulation of the gene. Our results indicate that synthesis of diapausin-1 is part of an antifungal innate immune response to infection in M. sexta . Highlights: An antifungal peptide, diapausin-1 was isolated from hemolymph of Manduca sexta larvae. Recombinant diapausin-1 was active against yeast and some ascomycete fungi. Diapausin-1 expression in fat body was strongly increased after larvae were injected with yeast.